Research on the Impact of Venture Capital Strategy on Enterprise Innovation Performance: Based on Evidence of Investment Timing and Rounds - Li, Xiwen; Zhao, Yunjia (Frontiers in Environmental Science, 2022)
Innovation is the first development force; thus, it is necessary to study the factors to enhance innovation ability. What type of venture capital strategy is more conducive to promoting enterprise innovation? We use the companies listed on the Growth Enterprise Market from 2009 to 2017 as samples and employ the Poisson regression method to empirically test the impact of venture capital investment timing and rounds of venture capital on entrepreneurial innovation performance. The results indicate that 1) venture capital can significantly improve firms’ innovation performance; however, compared with the early stage investment, the late-stage investment can significantly improve the firm’s innovation performance. With the increase in investment rounds, the innovation performance of enterprises is significantly improved. 2) Investment timing has a significant negative moderating effect on the relationship between investment rounds and firm innovation, that is, late-stage investment will significantly weaken the positive impact of investment rounds on firm innovation.